Extraordinary optical transmission by interference of diffracted wavelets - Kumar, Raj (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The phenomenon of extraordinary optical transmission is drawing much attention of researchers because of its potential applications in diverse emerging areas. In the present work, experimental observations on diffraction-Lloyd-mirror interferometer are reported, where two diffracted wavefronts are superimposed using Lloyd’s mirror. These observations provide direct experimental evidence in support of the idea that one of the main reasons of enhanced transmission through subwavelength apertures is the coherent superposition of diffracted wavelets originating from diffractive scattering at the apertures.
Optica Applicata, Vol. 40, 2010, nr 2, s. 491-499
Keywords: optyka; extraordinary optical transmission; diffraction